2007
DOI: 10.1007/s00701-007-1259-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive assessment of shunt effectiveness in patients with idiopathic normal pressure hydrocephalus by determining regional cerebral blood flow on 3D stereotactic surface projections

Abstract: The preoperative measurement of rCBF by 3D-SSP SPECT may help to identify iNHP patients expected to exhibit a good response to shunt operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 23 publications
3
31
1
Order By: Relevance
“…This finding is consistent with the cognitive features of subcortical dementia, which arises from disruption of the frontal-subcortical circuits [23,24,25]. Previous neuroimaging studies have reported that frontal cortical grey matter volume is preserved, but frontal regional cerebral blood flow (rCBF) is decreased in iNPH patients [26,27,28,29]. These findings support the view that frontal lobe-like cognitive dysfunction in iNPH is associated with subcortical white matter damage but not frontal lobe damage itself.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is consistent with the cognitive features of subcortical dementia, which arises from disruption of the frontal-subcortical circuits [23,24,25]. Previous neuroimaging studies have reported that frontal cortical grey matter volume is preserved, but frontal regional cerebral blood flow (rCBF) is decreased in iNPH patients [26,27,28,29]. These findings support the view that frontal lobe-like cognitive dysfunction in iNPH is associated with subcortical white matter damage but not frontal lobe damage itself.…”
Section: Discussionsupporting
confidence: 81%
“…Although our study was performed on iNPH brains, and was a CBF study, not a glucose metabolism study, the same phenomenon may be seen in the brains of patients with motor dysfunction. Murakami et al [19] reported that shunt responders manifested significantly lower CBF in the basal frontal lobes and cingulate gyrus in a comparison of 14 shunt responders with 10 shunt nonresponders, although our study did not show such differences in a large sample study, except for a decreased CBF in the right medial basal frontal region in the favorable outcome group compared with the unfavorable group. Klinge et al [20,21] reported significantly reduced CBF in the frontobasal cortex in responders compared with nonresponders.…”
Section: Discussioncontrasting
confidence: 52%
“…On the other hand, the mean z-score for the precentral gyrus was significantly lower in the FOG group than in the non-FOG group, possibly because rCBF in the precentral gyrus increased to compensate for ACC dysfunction in the FOG group. The rCBF reduction in the ACC is also reportedly observed in PSP [35] and INPH [36]. Although the association between the FOG and the ACC was not examined in earlier reports, it is noteworthy that rCBF reduction in the ACC is common in diseases characterized by FOG.…”
Section: I-imp Spect In Pd Patients With and Without Fog Matched For mentioning
confidence: 64%